HUBUNGAN TINDAKAN BUNUH DIRI DENGAN KESEHATAN MENTAL DI INDONESIA - Meta Zulyati Oktora; Putri Suryani Puspita Dewi; Mutiara Annisa (Nusantara Hasana Journal, 2024)
Introduction: Suicide is one of the causes of death that often occurs in individuals who have mental disorders. Suicide can start from depression that occurs in the sufferer. Spiritual aspects are often associated with preventing suicidal behavior. Several related studies have explained how spiritual support can reduce levels of depression in individuals. Method: This literature review aims to determine the role of spirituality in influencing the risk of suicidal behavior in adults. Writing this journal uses a literature study approach originating from a database, namely Google Scholar using keywords. Filtered 159,320 journals and managed to find 14 related journals. Using inclusion criteria which include literature sources taken from 2018 to 2023, using Indonesian, appropriateness of writing keywords, relevance of literature writing results to the discussion raised. Results: Mental health problems such as depression which cause the risk of suicide can be overcome with psychosocial and religious interventions in order to create good copying in solving individual problems. Several interventions provided to treat individuals with mental health problems who are at high risk of suicidal behavior include the Social Spiritual Group (SSG) which can be applied to health services (Forrester-Jones, Dietzfelbinger, Stedman, & Richmond, 2018). Psychosocial support also often helps reduce patients’ depressive symptoms and possible risk of suicide, and has been shown to improve psychological well-being. Conclusion: Suicide attempts often occur, both among teenagers, adults and the elderly. This behavior is not only increasing sharply in Indonesia, but almost throughout the world. Before taking action on a cooperative patient, do not deny that there has been a suicide attempt. However, the client speaks slowly and finds it difficult to start a conversation. Clients also do not understand the coping patterns that can be applied when clients face a problem.